Prevalence, Incidence, and Sensitization Profile of β-lactam Antibiotic Allergy in Hong Kong - Li, Philip H. (JAMA Netw Open, 2020)
IMPORTANCE: Allergy to β-lactam antibiotics is one of the most frequently reported drug reactions, but epidemiological data in Chinese populations are lacking. Ethnic- and region-specific sensitization patterns of skin testing for β-lactam antibiotic allergy are also unknown. OBJECTIVE: To identify the prevalence, 1-year incidence, and sensitization patterns of β-lactam antibiotic allergy in patients in Hong Kong. DESIGN, SETTING, AND PARTICIPANTS: This cross-sectional study obtained territorywide, anonymized electronic patient data from the Clinical Management Systems of the Hospital Authority, the sole publicly funded health care system in Hong Kong with facilities in 7 regions (Hong Kong East, Hong Kong West, Kowloon Central, Kowloon East, Kowloon West, New Territories East, and New Territories West). All referrals to Queen Mary Hospital for β-lactam antibiotic allergy testing from January 1, 2018, to December 31, 2019, were also analyzed for sensitization patterns. MAIN OUTCOMES AND MEASURES: Prevalence and cumulative incidence of β-lactam antibiotic allergy reported in Hong Kong, and sensitization patterns according to β-lactam antibiotic allergy skin testing. RESULTS: Complete records of 7 184 271 unique patients were analyzed, with a men to women ratio of 1:1.2 and with a median age of 44 years. The prevalence of physician-reported β-lactam antibiotic allergy was 2.0%, and the cumulative incidence was 107 per 100 000 population. Of the 34 402 new drug allergies reported in 2018, 8032 (23.3%) were β-lactam antibiotic allergies. Three hundred fifty-five patients with reactions suggestive of β-lactam antibiotic allergy underwent skin testing, and only 49 (13.8%; 95% CI, 10.64%-17.90%) of them had positive test results. Of these 49 patients, 14 (28.6%; 95% CI, 18.35%-44.49%) had selective reaction and 35 (71.4%; 95% CI, 59.84%-85.27%) had nonselective reaction. The sensitization rate to either benzylpenicilloyl polylysine or a minor determinant (benzylpenicilloate) was 47.0% (n = 23; 95% CI, 34.85%-63.21%), with 10 patients monosensitized to benzylpenicilloyl polylysine only (20.4%; 95% CI, 11.74%-35.48%) and 5 to benzylpenicilloate only (10.2%; 95% CI, 4.45%-23.42%). CONCLUSIONS AND RELEVANCE: Results of this study suggest that patients in Hong Kong with β-lactam antibiotic allergy had much higher rates of monosensitization to benzylpenicilloyl polylysine and benzylpenicilloate, making these reagents essential in β-lactam antibiotic skin tests. Such a finding warrants future studies into whether this sensitization is specific to ethnicity or region.